Effects of Gyroscope on Arm Swing and Gait in Healthy Volunteers - Meriç Selim Şipal; Elif Yalçın; Aynur Ayşe Karaduman (Applied Bionics and Biomechanics)
Background. Arm swing has a crucial role in gait. It is essential in terms of regulating gait parameters and balance during walking. In the case of bradykinesia, the arms act as a generator to maintain lower extremity movement while walking. The way gyroscopes work makes them useful in arm swings. In this study, the arm swing is facilitated by a new type of gyroscope. As a main purpose, a gyroscope was used to increase arm swing during pendulum exercise and walking. Methods. Thirty healthy volunteers were included in the study. The study covered three situations. The first evaluation was performed without the gyroscope. The second evaluation was performed while the gyroscope was installed but not activated. The final evaluation was made while the gyroscope was installed and powered up. The effect of the gyroscope on the arm swing was evaluated by the Dartfish®, and the gait was evaluated with the Zebris® force distribution measurement analysis system. Results. According to the results, the gyroscope increases the arm swing in the pendulum exercise (p<0.05). Furthermore, using the gyroscope, the step width decreased, and the gait cycle time increased (p<0.05). Conclusions. The gyroscope is suitable for facilitating arm swings in healthy volunteers. This study is essential to demonstrate the effect of a gyroscope on extremity movements for the first time. In the future, a medical device that has the features of a gyroscope can be designed for its use in the treatment of Parkinson’s disease and Senile Bradykinesia.